2008
DOI: 10.1055/s-2008-1076961
|View full text |Cite
|
Sign up to set email alerts
|

Risikoprofil und Rezidivprophylaxe der Narbenhernie – was ist evidenzbasiert?

Abstract: Incisional hernia is a late complication of laparotomy for which an evidence-based prohylactic approach is still lacking. Postoperatively, incisional hernias occur because of multiple factors. Preoperative comorbidities belong to these risk factors. A risk reduction related to concomitant diseases mostly does not succeed. There is a range of studies comparing the techniques of surgical wound closure. A consensus of these is that a running suture of the fascia with slowly absorbable or non-absorbable sutures re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…The importance of meticulous abdominal wall closure cannot be disregarded in this context. Evidence shows that maintaining a suture length–wound length ratio of 4:1 [ 26 , 27 ], using a continuous suture with slowly absorbable or non-absorbable suture material [ 26 , 28 37 ], maintaining a distance from needle puncture to wound edge of at least 1 cm [ 30 ], as well as distances of less than 1 cm between two punctures [ 31 ], can reduce the incidence of incisional hernia. Ever since the publication of works by Israelsson in the mid 1990s, it has been the accepted wisdom that less can be more: by using smaller needles and small tissue bites, incisional hernia incidence in medial laparotomy following aortic aneurysm repair can be reduced from 21% to 10% ( p < 0.01), and to as little as 5.2% in selected patients [ 11 , 31 – 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of meticulous abdominal wall closure cannot be disregarded in this context. Evidence shows that maintaining a suture length–wound length ratio of 4:1 [ 26 , 27 ], using a continuous suture with slowly absorbable or non-absorbable suture material [ 26 , 28 37 ], maintaining a distance from needle puncture to wound edge of at least 1 cm [ 30 ], as well as distances of less than 1 cm between two punctures [ 31 ], can reduce the incidence of incisional hernia. Ever since the publication of works by Israelsson in the mid 1990s, it has been the accepted wisdom that less can be more: by using smaller needles and small tissue bites, incisional hernia incidence in medial laparotomy following aortic aneurysm repair can be reduced from 21% to 10% ( p < 0.01), and to as little as 5.2% in selected patients [ 11 , 31 – 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The suture material and suture technique used to close the fascia have been shown to affect the risk of incisional hernia in midline incisions. A suture technique with continuous sutures placed 1 cm apart and 1 cm from the incision using a suture 4 times the length of the incision has been shown to prevent hernias [31] . Additionally, a meta-analysis found that slowly absorbable suture material caused fewer hernias [32] .…”
Section: Discussionmentioning
confidence: 99%
“…auch als "Kasuistik" und "Sonderbeitrag" zunehmend auch wieder aus der experimentellen Chirurgie zu behandeln. Damit soll eine sinnvolle, geeignete und anknüp-fende Ergänzung von bereits im Journal "Zentralbl Chir" publizierten Aspekten, wie auch zum anstehenden Themenschwerpunkt ausgewiesen [1][2][3][4][5][6], möglichst mit einer Vielzahl von Artikeln erreicht werden, um damit eine Kontinuität der Themenbehandlung und Wissensvermittlung noch besser, aktuell und kompetent auszuweisen bei wirksamer Vermeidung zeitnaher inhaltlicher Wiederholungen. Interessante Themenhefte sind in dieser Hinsicht für 2012 vorgesehen, die " in bewährter Form chirurgische Kongresshöhepunkte (u. a. DGC-Jahreskongress, DGG-Jahreskongress, DGAV-Jahreskongress) entsprechend des verfolgten Themenprofils der Zeitschrift würdigen, als auch " neue originelle und aktuelle Themenkomplexe in den nächsten 6 "Zentralblatt-für-Chirurgie"-Ausgaben aufgreifen im kompetitiven chirurgisch-publizistischen Betätigungsfeld durchaus auch in Reflexion auf mögliche internationale Ausstrahlung mit Kompetenz-bzw.…”
Section: Editorial 563unclassified